Propuesta de dotaciones de agua potable para poblaciones menores a 150000 habitantes del Ecuador, basada en las caracteristicas meteorologicas y socio-economicos. - Bayas Urquizo, José Andrés (2018)
The water supply service contributes to the development of a population, so great attention must be given to its distribution. Within the Ecuadorian territory, the supply of drinking water can be made through provisions established in the regulations. Ecuadorian Code of Construction (CCA, 1992). This standard shows images with several populations interested in the supply of drinking water. This standard defines the climate and the size of the population as the indicators under which the selection that best fits the characteristics of the population is selected. However, the ranges of both aspects are not well defined or, at times ambiguous. The current norm does not consider social aspects and customs, the same ones that influence the consumption of water. Why it is not known if there is a relationship of socioeconomic and meteorological characteristics with drinking water consumption. This research is based on 9 investigation of domestic water consumption, associated with meteorological, socioeconomic and habitat factors in 11 populations, statistically establishes drinking water consumption for populations of less than 150,000 inhabitants, based on meteorological and socio-economic aspects. With the consumption of drinking water. The research data was processed, using the statistical software R to determine the linear correlations of the statistics, and this is established in the meteorological, social or customs factors area related to water consumption. The relationship between demography and drinking water consumption was established, creating a nonparametric mathematical model, which explains 62.45% of drinking water consumption according to population size.